A Computational Model of Tumor Growth and Anakoinosis - Pan Pantziarka; Pan Pantziarka; Lina Ghibelli; Albrecht Reichle (Frontiers Media S.A., 2019)
Anakoinosis is a new cancer treatment paradigm that posits a key role for communicative reprogramming within tumor systems. To date no mathematical or computational models of anakoinosis have been developed. Here we outline the NEATG_A system, a first computational model of communicative reprogramming. The model recapitulates key features of real tumor systems and responses to both traditional cytotoxic treatments and biomodulatory/anakoinotic treatments. Results are presented and discussed, particularly with respect to the implications for future cancer treatment protocols.